Alcohol drinking in university students matters for their self-rated health status: A cross-sectional study in three European countries - Rafael T Mikolajczyk; Rafael T Mikolajczyk; Rene Sebena; Julia Warich; Vihra Naydenova; Ursula Dudziak; Olga Orosova (Frontiers Media S.A., 2016)
Background:Alcohol drinking was linked to self-rated health in different populations, but the association was inconsistent. We studied the association among university students across three European countries with different patterns of drinking. Methods:We analysed data from three universities, one from each country: Germany (beer dominant), Bulgaria (wine dominant) and Poland (unclassified among youths, spirits dominant in adults) (N=2103). Frequency of drinking and problem drinking (two positive responses on CAGE-scale) on the one side and self-rated health, caring for ones own health and worsening of health since the last year on the other side were assessed by means of self-administered questionnaire. The association between alcohol- (independent) and health-related (dependent) variables was evaluated by means of logistic regression, adjusting for country and sex. Results:Poor self-rated health and worsened health since previous year were associated only with problem drinking (odds ratio 1.82 (95% confidence interval [CI] 1.21-2.73) and 1.61 (95% CI 1.17-2.21), respectively), but not with a higher frequency of drinking. In contrast, not caring for one's own health was associated with frequent drinking (1.40 (95% CI 1.10-1.78)) but not with problem drinking (1.25 (95% CI 0.95-1.63)). The results were consistent across the studied countries and by sex. Conclusions:The health status of university students was associated with problem drinking. A high frequency of drinking was associated with the lack of care of own health, but it was not associated with current health status. These associations were independent of the predominant pattern of drinking across the studied countries.